Cover Picture: Ergoline‐Derived Inverse Agonists of the Human H3 Receptor for the Treatment of Narcolepsy (ChemMedChem 8/2014). Issue 8 (August 2014) - Auberson, Yves P.; Troxler, Thomas; Zhang, Xuechun; Yang, Charles R.; Fendt, Markus; Feuerbach, Dominik; Liu, Yu‐Chih; Lagu, Bharat; Lerchner, Andreas; Perrone, Mark; Lei, Lijun; Zhang, Chao; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows (6aR, 9R)‐4‐(2‐(dimethylamino)ethyl)‐N‐phenyl‐9‐(pyrrolidine‐1‐carbonyl)‐6, 6a, 8, 9‐tetrahydroindolo[4, 3‐fg]quinoline‐7(4H)‐carboxamide (23) and its effect on wakefulness in mice. Compound 23 represents a novel class of histamine H3 receptor (H3R) inverse agonists based on an ergoline scaffold. It rapidly penetrates the brain, blocks H3Rs, and enhances wakefulness with a short duration of action. This profile is required to mitigate the episodes of insomnia documented with previously reported clinical candidates during the night following administration. For more details, see the Full Paper by Yves P. Auberson, Thomas Troxler, Xuechun Zhang et al. on p. 1683 ff. The images of asleep and awake mice were adapted from photos published on flickr.com under a CC‐BY license by the U.S. Fish and Wildlife Service (USFWS) and Spencer Wright, respectively.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>